2020
DOI: 10.4187/respcare.07715
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Continuous Infusion Aerosol Delivery During Mechanical Ventilation

Abstract: Brook holds patents in the fields of nebulizer development and inhaled antibiotic delivery which have been licensed to InspiRx. Dr. Smaldone is a consultant to InspiRx and is a member of the Advisory Board; Ms. Cuccia serves as a consultant to InspiRx, Inc.; Mr. McPeck and Dr. Ashraf have no conflicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Use of a radioactive tracer coupled with the gamma camera provides a detailed assessment of inhaled drug delivery in a mechanical ventilation circuit. ( 7 , 9–11 ) However, in previous studies, analysis of an experiment could not begin until after it was completed, and IM separately measured. Nebulizer function and aerosol output of some nebulizers in a ventilator circuit may be difficult to observe, and if aerosol output differs from that expected, the question always remained “did the nebulizer function?” The effect of anomalies on the veracity of the experiment often could not be determined in real time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of a radioactive tracer coupled with the gamma camera provides a detailed assessment of inhaled drug delivery in a mechanical ventilation circuit. ( 7 , 9–11 ) However, in previous studies, analysis of an experiment could not begin until after it was completed, and IM separately measured. Nebulizer function and aerosol output of some nebulizers in a ventilator circuit may be difficult to observe, and if aerosol output differs from that expected, the question always remained “did the nebulizer function?” The effect of anomalies on the veracity of the experiment often could not be determined in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, with this particular nebulizer, the heated humidifier did not present as a significant barrier to aerosol delivery as has been shown in other studies. ( 7 , 9 , 10 ) The mass balance is therefore an important aspect of in vitro aerosol delivery assessment because (i) it accounts for all the drug or tracer placed initially or infused into the nebulizer over time, and (ii) its distribution has the potential to vary depending on several factors, alone and in combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, there is no consensus on whether a nebulizer should be combined with a humidifier, and if the humidifier should be placed between nebulizer and patient or the other way around ( 32 , 33 ). Therefore, the effect of epoprostenol and iloprost was measured in relation to the nebulizer position.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of gravitational feed was noted as well as bubble formation on the mesh particularly when used during mechanical ventilation. ( 66 , 67 ) In the IASIS trial, an inline vibrating plate electronic nebulizer (eFlow Inline System; PARI GmbH) was used. ( 5 ) Rottier et al tested PARI eFlow devices and found >50% of the time the eflow switched off after 19 minutes.…”
Section: Designing Clinical Trials For Ventilator-associated Infectionmentioning
confidence: 99%